PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN BERHITUNG ANAK AUTIS SEKOLAH DASAR - Emma Nanda Putri, Shefrielia (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: One of the problems in the cognitive field of autistic children is a mathematical ability that includes numeracy materials.  Realistic Mathematics Education (RME) approach is a math learning alternatives that will facilitate children in learning mathematics by using concrete objects or will make a real and meaningful learning. The developed aspect is the ability to count and addition of 1 to 20 deductions. The research method is by using quantitative research approach to the type of pre-experimental study, and the study design of one-group pretest-posttest. Subjects in this study were 6 children with autism in SDN Klampis Ngasem 1 Surabaya. This study aims to determine the effect of Realistics  Mathematics Education (RME) approach to the numeracy skills of children with autism in SDN Klampis Ngasem 1 Surabaya. Data collection techniques are in the form of observation, test and documentation. Whereas statistical data analysis techniques used non-parametric Wilcoxon test. The results showed the initial test / pre-test average obtained 46.65 and the final test / post-test average is 80. This indicates that there is a significant increase. Zh value = 2.20 is greater than 5% value crisis Zt = +1.96 which means that Ho is refused and Ha is received so that, it can be said as the influence of the Realistic Mathematics Education (RME)approach to the numeracy skills of children with autism in SDN KlampisNgasem 1 Surabaya.   Keywords:  Realistic Mathematics Education (RME) approach, Numeracy Skill.